Exploring Muslim Women Pioneers Who Contributed to the Glory of Islamic Civilization from the Advent of Islam to the End of the 13th Century AH (19th Century CE) - Mohammed Houmine (International Journal of Islamic Khazanah)
The West's view of Muslim women is not devoid of attitudes that relegate them to a kind of inferiority, as enslaved and humiliated, whose main task is to reproduce, educate, cook, wash and so on. In fact, the word "harem" is almost never far from these epithets. Therefore, this article aims to dust off the glorious history of Muslim women as contributors, alongside their male counterparts, in building the edifice of the glorious Islamic civilisation throughout the ages. It also aims to help erase the stereotypical image of Muslim women. Through historical, social and intellectual approach, and focusing on a review of the sources adopted by researchers on the subject, whether Muslim, Orientalist or Western, we recall their contributions in all fields of public life, including political, cultural, scientific, medical, teaching, construction, writing and others. As these previous studies rarely addressed the issue in all its aspects, as many of them were limited to certain areas, this research, although not exhaustive, aims to be as comprehensive as possible in all the areas in which Muslim women have excelled. The finding shows that this later had an independent personality and financial status, and never needed the Charter of Women's Rights, which was drafted in the twentieth century. Other sources have not yet been investigated. It is hoped that further research will be carried out in the future